Teacher Assistance In Children's Learning Innovation at Madrasah Ibtidaiyah Takhasus Al-Qur'an Sintang - Nijo, Nijo; Boy, Boini; Ihsan, Muhammad; Sahrul, Sahrul; Asmanah, Asmanah; Muttaqin, Imron (The Magister of Islamic Education IAIN Pontianak, 2025)
This article discusses the strategic role of teacher mentoring in encouraging innovation in children's learning at Madrasah Ibtidaiyah Takhasus Al-Qur'an Sintang. This research is motivated by the need to create an active, participatory, and relevant learning process with student characteristics. The results of the study show that teachers provide mentoring through various innovative approaches, such as group learning, providing opportunities for students to re-present the material, and encouraging students to ask questions actively. This approach is in line with the theory of constructivism and social learning which emphasizes the importance of student interaction and involvement in the learning process. However, teachers also face challenges in the mentoring process, including delays in students' understanding of the material, uneven reading skills, and easily distracted student concentration. These obstacles require teachers to be more adaptive and creative in managing learning. The conclusion of this article emphasizes that teacher mentoring that is carried out continuously and innovatively is an important key in improving the quality of learning, as well as forming students' learning characters who are more independent and critical.